Level of physical fitness of member of Indonesian Medical Association in Bantul, Yogyakarta - Ihsana, Nuni; Yuniasih, Dewi; Putri, Rachma Greta Perdana; Annisa, Annisa; Tejosukmono, Ario; Heriyanto, Mochammad Junaidy; Pamungkasih, Wahyu; Rokhmah, Budi Nur; Murdiyanto, Joko (Ahmad Dahlan Medical Journal, 2024)
Physical inactivity contributed to 7.2% of all-cause mortality. Many research demonstrates that the integration of physical activity and exercise into daily routine prevents chronic disease and lowers mortality. This study aims to assess the physical fitness of members of the Indonesian Medical Association in the Bantul region using a descriptive from secondary data. The subjects were 38 members of the Indonesian Medical Association. Physical fitness data was obtained using the Rockport One Mile Walking Test. Body Mass Index (BMI) is also calculated to describe excessive body fat. The majority of participants are female (52.63%) and participants dominant age ranged between 19 and 44 years old (50%). The participants aged 18 years old showed good physical fitness. The results in participants aged 19 to 44 years were more varied, there were 8 participants, 7 participants, 3 participants 1 participant had fair, good, poor, and very poor physical fitness, respectively. Physical fitness in participants aged 45 to 59 years were 9 and 5 participants showed good and fair physical fitness, respectively. The subjects aged >59 years old have 2 people with good physical fitness and 1 person with fair physical fitness. None of the participants with BMI status underweight, normal weight, or overweight showed poor physical fitness, while participants with obesity had poor and very poor physical fitness. Physical fitness is a multidimensional concept and is related to regular activity.